Rural tourism and its geospatial organization in Poltava region - Shukanova, Angela; Vishnikina, Liubov; Fediy, Oleksandr (The Journal of V. N. Karazin Kharkiv National University. Series: International Relations. Economics. Country Studies. Tourism, 2020)
The article is devoted to the current problem of rural tourism development at the national and regional levels. The paper reviews publications dedicated to rural tourism, which proved that the study of the development and geospatial organization of rural tourism in Poltava region requires further research. It analyzes the domestic legal framework, which is the basis for the development of rural tourism, covers scientific approaches to the conceptual and terminological apparatus of rural tourism and systematizes objects of tourist interest. According to the results of the study, the interpretation of the concept of "rural tourism" in a narrow subject sense (a form of recreational and tourist non-professional entrepreneurship of rural residents in rural areas while preserving their natural and cultural identity with a demonstration of traditional rural lifestyle) and in a broad sense (any forms of leisure time for tourists and excursionists in rural areas, as areas outside the city, including meadow-forest areas and water areas) was cleared up. In order to single out rural tourism accommodation establishments, it was proposed to follow the Minimum International Quality Standards of the European Rural Tourism Federation EuroGites, adapted to the types of settlements accepted in Ukraine. On the example of Poltava region the variety of offers of types of rural tourism estates as per prevailing services was summarized. According to open Internet sources and official data of Poltava regional and district state administrations, a map Estates and Services of Rural Tourism in Poltava Region was built; based on its analysis 6 centers of rural tourism of the region (Opishnya, Dykanka, Novy-Sanzhary, Velyka Bagachka, Kremenchug, Berezova Rudka) and their tourist specialization were singled out. Reshetylivka district is named as the most promising, but not realized in the sphere of rural tourism. Potential trends of rural tourism in Poltava region were determined.